LEGAL STUDY OF DEFENSE STRATEGIES IN CRIMINAL CASES BASED ON ELECTRONIC EVIDENCE - Muhammad Rusdi; Sunardi Purwanda; Muhammad Sabir Rahman; Bakhtiar Tijjang; Aksah Kasim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine and analyze the legal qualifications in the Criminal Procedure Code and the ITE Law regarding electronic evidence in criminal cases in Indonesia and effective defense strategies in facing electronic evidence-based criminal cases by adapting to the new criminal law system. This study uses a Normative research type with a Legislative Approach and a Conceptual Approach. The types of legal material sources use Primary legal materials, Secondary legal materials and Tertiary legal materials. Legal analysis will be studied in a qualitative prescriptive manner. The results of this study are the legal qualifications in the Criminal Procedure Code and the ITE Law regarding electronic evidence in criminal cases in Indonesia, namely the Legal Qualification of Electronic Evidence based on Law Number 20 of 2025 concerning the Criminal Procedure Code, namely formally recognized as evidence, obtained legally and authentically (original and not changed/manipulated) and materially related to the crime and the identity of the perpetrator. While the legal qualifications according to the 2024 ITE Law are Valid as evidence, Obtained legally. and Obtained from a secure and tested electronic system, Electronic evidence must be original (authentic), unchanged (integrity) and trustworthy (reliability) and Must be related to the case and Effective defense strategies in facing electronic evidence-based criminal case evidence by adapting to the new criminal law system, namely Delegitimization of electronic evidence, Reclassification of evidence, Testimonium de Auditu Digital attacks, Analysis of evidence linkages, psychological attacks and suggestions and Alternative narratives.